Assessment of the feed additives thiamine hydrochloride (3a820) and thiamine mononitrate (3a821) (vitamin B1) for all animal species for the renewal of their authorisation (DSM Nutritional Products Ltd. and Orffa Additives BV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of vitamin B1 (thiamine hydrochloride and thiamine mononitrate) for the renewal of its authorisation as nutritional feed additive for all animal species. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that vitamin B1 remains safe for all animal species, consumers and the environment. Thiamine mononitrate is not irritant to the eyes, while hydrochloride is not irritant to skin, but it is irritant to the eyes. Both salts of thiamine are considered skin and respiratory sensitisers, and any exposure is considered a risk. These conclusions would apply, in principle, to any preparations produced with the thiamine mononitrate. The Panel concluded there is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.